2020
DOI: 10.1101/2020.03.31.017707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin 3D interaction analysis of theSTARD10locus unveilsFCHSD2as a new regulator of insulin secretion

Abstract: Genome-wide association studies have identified thousands of genetic variants associated with type 2 diabetes (T2D) risk. Using chromatin conformation capture we show that an enhancer cluster in the STARD10 T2D locus forms a defined 3D chromatin domain. A 4.1 Kb region within this region, carrying five disease-associated variants, physically interacts with CTCF-binding regions and with an enhancer possessing strong transcriptional activity. Analysis of human islet 3D chromatin interaction maps identifies FCHSD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Altogether, these data support the potential regulation of TTLL6 by NEUROG3. Interestingly, the NEUROG3 binding site assigned to the ARAP1 gene coincided with an islet active enhancer (R11, Figure 8E) belonging to a regulatory region of the STARD10 and FCHSD2 genes, highly enriched in T2D/FG variants [27; 62]. The variable region (VR) within this locus was demonstrated to be required for insulin secretion [62].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these data support the potential regulation of TTLL6 by NEUROG3. Interestingly, the NEUROG3 binding site assigned to the ARAP1 gene coincided with an islet active enhancer (R11, Figure 8E) belonging to a regulatory region of the STARD10 and FCHSD2 genes, highly enriched in T2D/FG variants [27; 62]. The variable region (VR) within this locus was demonstrated to be required for insulin secretion [62].…”
Section: Resultsmentioning
confidence: 99%
“…These data recapitulate the pattern of improved proinsulin processing observed at the human GWAS signal. STARD10 inactivation reduces GSIS both in mice ( 116 ) and in human EndoC-βH1 cells ( 117 ) and leads to profound changes in secretory granule structure in mouse beta cells ( 118 ). Solution of the 3D structure of STARD10 and direct binding assays revealed that STARD10 binds to and may transport inositol phospholipids, contributing to the failure of normal granule biogenesis in carriers of risk alleles (where STARD10 expression is lowered) ( 116 ).…”
Section: Variants Associated With Type 2 Diabetesmentioning
confidence: 99%
“…Nevertheless, as proof of concept, Ferrer’s group have demonstrated that alteration of variants containing enhancer activity by CRISPR interference affects the expression of multiple genes in EndoC-βH1 cells ( 48 ). Our own work, focusing on an enhancer cluster at the STARD10 locus, also showed that an enhancer cluster regulates not only STARD10 but also FCHSD2 through chromatin looping ( 117 ). Detailed analyses of how these and other variants affect chromatin structure, enhancer activity and gene expression are now warranted to elucidate the molecular mechanisms of disease pathways.…”
Section: Variants Associated With Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations